Terminal Goan Hoat: Sejarah dan Perannya Dalam Sistem Transportasi Di Padang (1972-2004). - Wahyudi Rusdianda; Meri Erawati; Kaksim (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The results of this study explain the history of the Goan Hoat Terminal at Pasar Raya Padang (1972-2004), supported by the condition of the terminal in Pasar Raya. The discussion on the Goan Hoat Terminal is divided into several parts, namely the Goan Hoat Terminal Before 1972 and the Goan Hoat Terminal as the City Transport Terminal (Angkot) in 1972-2004. Before 1972 the Goan Hoat Terminal was the only Inter-City In-Province Terminal (AKDP) in Padang City. In 1972-2004 the Goan Hoat Terminal was converted into a City Transportation Terminal (Angkot). During the reign of Mayor Fauzi Bahar, the city of Padang underwent a change in the Spatial Planning of the City of Padang which resulted in the Goan Hoat Terminal being converted again as a place of modern heaven known as the Central Pasar Raya Plaza (SPR Plaza) and the government moved the Aia Mancur Roundabout in front of the Muhammadiyah Mosque as a gathering place for all types of public transportation in Padang City which resulted in congestion at Pasar Raya Padang.